2019
DOI: 10.1371/journal.pone.0209593
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in prevalence and antithrombotic treatment among Asians with atrial fibrillation undergoing percutaneous coronary intervention: A nationwide Korean population-based study

Abstract: BackgroundWe investigated the recent 10-year trends in the number of patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI) in relation to prescription patterns of antithrombotic therapy.MethodsWe analyzed the annual prevalence of PCI and patterns of antithrombotic therapy after PCI, including antiplatelets and oral anticoagulants (vitamin K antagonists and non-vitamin K antagonist oral anticoagulants [NOACs]), in patients with AF between 2006 and 2015 by using the Korean Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…A recent report examining the prescription pattern of antithrombotic therapy in patients with AF undergoing PCI revealed that the number of patients with AF and PCI has increased constantly, but OAC prescription was only 40% in 2015. 32) Furthermore, more than 70% of patients received antiplatelet agents only one-year after PCI. 33) Considering that most of these patients have a high risk of stroke, optimal antithrombotic therapy may be necessary after PCI.…”
Section: Cardiovascular Researchers Using the National Health Informamentioning
confidence: 99%
“…A recent report examining the prescription pattern of antithrombotic therapy in patients with AF undergoing PCI revealed that the number of patients with AF and PCI has increased constantly, but OAC prescription was only 40% in 2015. 32) Furthermore, more than 70% of patients received antiplatelet agents only one-year after PCI. 33) Considering that most of these patients have a high risk of stroke, optimal antithrombotic therapy may be necessary after PCI.…”
Section: Cardiovascular Researchers Using the National Health Informamentioning
confidence: 99%
“…One study investigated the temporal trends of antithrombotic therapy in Korean AF-PCI patients during 2006 and 2015, whereby the proportion of TAT increased from 22.7% to 38.2%, but DAPT still comprised the largest proportion at 60.3%. 12) However, there is a caveat that this 10/14 https://e-kcj.org https://doi.org/10.4070/kcj.2020.0407…”
Section: Discussionmentioning
confidence: 99%
“…The authors considered that this might have been partly due to the relatively low prothrombin time–international normalized ratio (PT-INR) control (1.83 ± 0.41) in the study patients. Moreover, a nationwide Korean study showed the gradual increase in the prescription rate of TAT for patients with AF undergoing PCI [ 75 ]. Because the Japanese guideline recommends that a target PT-INR of 1.6–2.6 for patients with AF aged >70 years [ 76 , 77 ], a lower therapeutic level of warfarin with DAPT might be another option, especially for patients at high risk of thrombotic events including stent thrombosis.…”
Section: Optimal Antithrombotic Regimen In Patients With Af Undergmentioning
confidence: 99%